Occluding the face diminishes the conceptual accessibility of an animate agent - Rissman, Lilia; Woodward, Amanda; Goldin-Meadow, Susan (Language, cognition and neuroscience, 2019)
The language that people use to describe events reflects their perspective on the event. This linguistic encoding is influenced by conceptual accessibility, particularly whether individuals in the event are animate or agentive - animates are more likely than inanimates to appear as Subject of a sentence, and agents are more likely than patients to appear as Subject. We tested whether perceptual aspects of a scene can override these two conceptual biases when they are aligned: whether a visually prominent inanimate patient will be selected as Subject when pitted against a visually backgrounded animate agent. We manipulated visual prominence by contrasting scenes in which the face/torso/hand of the agent were visible vs. scenes in which only the hand was visible. Events with only a hand were more often associated with passive descriptions, in both production and comprehension tasks. These results highlight the power of visual prominence to guide how people conceptualise events.